From rock to living systems: Lanthanides toxicity and biological interactions - Marian Constantin; Mariana F. Chioncel; Livia Petrescu; Corneliu Ovidiu Vrancianu; Mihaela Paun; Roxana-Elena Cristian; Manuela Sidoroff; Mihai Viorel Dionisie; Mariana Carmen Chifiriuc (Ecotoxicology and Environmental Safety)
Since the discovery of lanthanides, the expanding range of applications and the growing demand for lanthanides in different aspects of life have escalated their dispersion in the environment, raising concerns about their impact on the living world. This review explores the interaction between lanthanides and different groups of living organisms (bacteria, algae, lichens, plants, invertebrates, and low vertebrates), reflecting the current state of scientific knowledge. We have aimed to provide a comprehensive overview of relevant studies, highlight existing gaps, and suggest potential areas for future research to enhance the understanding of this topic.